2007
DOI: 10.1007/s11157-007-9121-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the removal of organic micropollutants from wastewater in conventional treatment plants (CTP) and membrane bioreactors (MBR)

Abstract: As a consequence of insufficient removal during treatment of wastewater released from industry and households, different classes of organic micropollutants are nowadays detected in surface and drinking water. Among these micropollutants, bioactive substances, e.g., endocrine disrupting compounds and pharmaceuticals, have been incriminated in negative effects on living organisms in aquatic biotope. Much research was done in the last years on the fate and removal of those compounds from wastewater. An important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
1
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(188 citation statements)
references
References 132 publications
7
165
1
15
Order By: Relevance
“…In fact, significant variations in the removal of hydrophilic and biologically persistent compounds in the same study and between different studies have been reported in the literature for both MBR and CAS (Clara et al, 2005;Nakada et al, 2006;Tadkaew et al, 2011). Our results regarding the persistence of the above-mentioned six compounds are consistent with the results obtained from our own preliminary study (Nguyen et al, 2012) and other available studies (Clara et al, 2005;Joss et al, 2005;Urase et al, 2005;Nakada et al, 2006;Kimura et al, 2007;Cirja et al, 2008). Similarly, the presence of the strong electron-donating functional groups (such as hydroxyl and aliphatic) and/or absence of strong electron-withdrawing groups appear to be the reason of the high removal of the other hydrophilic compounds such as acetaminophen and salicylic acid , ibuprofen (Clara et al, 2005;Joss et al, 2005) and estriol (Urase et al, 2005;Hai et al, 2011) (Clara et al, 2005;Joss et al, 2005;Urase et al, 2005;Hai et al, 2011).…”
Section: Removal By Mbr Treatmentsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, significant variations in the removal of hydrophilic and biologically persistent compounds in the same study and between different studies have been reported in the literature for both MBR and CAS (Clara et al, 2005;Nakada et al, 2006;Tadkaew et al, 2011). Our results regarding the persistence of the above-mentioned six compounds are consistent with the results obtained from our own preliminary study (Nguyen et al, 2012) and other available studies (Clara et al, 2005;Joss et al, 2005;Urase et al, 2005;Nakada et al, 2006;Kimura et al, 2007;Cirja et al, 2008). Similarly, the presence of the strong electron-donating functional groups (such as hydroxyl and aliphatic) and/or absence of strong electron-withdrawing groups appear to be the reason of the high removal of the other hydrophilic compounds such as acetaminophen and salicylic acid , ibuprofen (Clara et al, 2005;Joss et al, 2005) and estriol (Urase et al, 2005;Hai et al, 2011) (Clara et al, 2005;Joss et al, 2005;Urase et al, 2005;Hai et al, 2011).…”
Section: Removal By Mbr Treatmentsupporting
confidence: 92%
“…However, MLVSS/MLSS ratio, supernatant turbidity, SVI and SOUR values were all stable throughout the study (Supplementary Data Table S5), suggesting continuous biological stability. Notably, at a significantly long sludge retention time, as applied in this study, slow-growing microorganisms, which may achieve efficient degradation of trace organic contaminants, can have the opportunity to proliferate in the bioreactor (Cirja et al, 2008). Performance of the MBR with respect to the removal of TOC and TN was stable during the entire study (Supplementary Data Table S5).…”
Section: Performance Stability and Toc/tn Removalmentioning
confidence: 89%
“…Depending both on the particular technology resorted to and the active substance properties they may undergo: (i) degradation (mineralization) to low molecular weight compounds (e.g. CO2 and water); (ii) entrapment by suspended solids; (iii) discharge of the parent compound through chemical cleavage of the respective con-jugate forms and (iv) conversion to a more hydrophilic, persistent form which will short-circuit the treatment process [39,41,56,57]. Thus, in hospitals use of specific antibiotics, antineoplasic or diag-nostic agents subsequently requires a sewage treatment process more embracing and directed to these kind of drugs, which are only used in hospitals [35,58], and that must be different to the more specific procedure adopted at STPs receiving industrial discharges from drug manufactures [47][48][49]59].…”
Section: Environmental Fatementioning
confidence: 99%
“…In the quest to enhance micropollutant removal, to date the effects of operational parameters such as HRT, SRT, pH and temperature on the removal efficiency of micropollutants by MBR treatment have been extensively studied (Cirja et al, 2008). However, as a notable omission, little is known about the effects of dissolved oxygen (DO) concentration on the removal of micropollutants by MBR treatment.…”
Section: Introductionmentioning
confidence: 99%